2005
DOI: 10.1158/1535-7163.mct-04-0238
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the epidermal growth factor receptor increases expression of genes that stimulate inflammation, apoptosis, and cell attachment

Abstract: The epidermal growth factor receptor (EGFR) is overexpressed in several types of human cancer, and inhibition of EGFR function is a promising strategy for cancer therapy. We used cDNA microarrays to examine alterations in gene expression after treatment of carcinoma cells with PD153035, a specific and reversible inhibitor of EGFR function. When human cervical carcinoma cells were grown on a collagen substrate in three-dimensional organotypic culture, untreated cells expressed high levels of EGFR RNA and invade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 45 publications
3
66
0
2
Order By: Relevance
“…EGFR is a receptor tyrosine kinase which can activate a number of downstream signaling pathways (reviewed in reference 10). It has been shown that inhibition of EGFR increases the expression of proinflammatory and apoptotic genes (46). Our finding that EGFR shows decreased activity during P2 infection and increased activity at 6 days following P18 infection is consistent with our hypothesis that P2 facilitates a normal, proinflammatory response early in infection, allowing clearance of the virus.…”
Section: Discussionsupporting
confidence: 91%
“…EGFR is a receptor tyrosine kinase which can activate a number of downstream signaling pathways (reviewed in reference 10). It has been shown that inhibition of EGFR increases the expression of proinflammatory and apoptotic genes (46). Our finding that EGFR shows decreased activity during P2 infection and increased activity at 6 days following P18 infection is consistent with our hypothesis that P2 facilitates a normal, proinflammatory response early in infection, allowing clearance of the virus.…”
Section: Discussionsupporting
confidence: 91%
“…The pathophysiology of this new dermatologic entity has not been fully elucidated, but the leading hypothesis is that the keratinocytes of the basal layer of the epidermis react to EGFR inhibition by secreting cytokines that trigger an inflammatory response that eventually causes loss of skin barrier protection and secondary skin infections involving mainly the hair follicles (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is highly expressed in many tumours, including those of the cervix, and there is a clear relationship between HPV E6/E7 oncoproteins and EGFR function (Hu et al, 1997). Blockade of EGFR in cervical cancer cell lines induces increased expression of genes that stimulate apoptosis and suppresses experimental metastasis (Kim et al, 2004;Woodworth et al, 2005). Fibroblast growth factor 1 (FGF1) is a growth factor for both tumour and stromal (endothelial) cells and induces the expression of matrix metalloproteinases (MMPs) and angiogenesis in cancer, hence its involvement in tumour progression (Aonuma et al, 1998;Kwabi-Addo et al, 2004;Udayakumar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%